Perilaku Masyarakat Jakarta Dalam Mengadopsi Sistem E-Government: Penggunaan Mobile Jaminan Kesehatan Nasional - Fatkhuri, Fatkhuri; Razaqa, Dhafin Faza; Azzahra, Bunga Indriani; Anisti , Caritas Nadya; Ivansyach, Raissa Kevin (Jurnal Ilmu Sosial, Humaniora dan Seni, 2025)
This study examines public behavior in adopting e-government services through the Mobile JKN application in the Jakarta area as a form of digitalization of public services in the health sector. The adoption of this application reflects the dynamics of the relationship between the state and citizens in the context of bureaucratic modernization, as well as the extent to which the public is willing and able to accept digital innovations offered by the government. This study aims to analyze the factors that influence the use of Mobile JKN and identify the obstacles faced by the community. A qualitative approach with a literature study method was used to collect data from relevant secondary sources, then analyzed descriptively. The results of the study indicate that the level of digital literacy, quality of application services, and social and cultural factors are the main determinants of adoption behavior. Obstacles such as lack of socialization, limited access to technology, and negative perceptions of government digital services also hamper the process of digitalization of services. This study contributes to the development of political science, especially in understanding the relationship between the state and society in digital public policy and the importance of a participatory approach in the transformation of public services.